Leverage as Moderation on the Effect Firm Size, Managerial Ownership and Conflict of Interest on Accounting Conservatism - Nadia Amanda Putri; Rizka Destiana (Journal of Applied Accounting and Taxation, 2025)
This study examines how firm size, managerial ownership, and conflict of interest influence the application of accounting conservatism, with leverage as a moderating variable. The population studied comprised 125 manufacturing companies in the non-cyclical consumer sector, listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. Using purposive sampling, 41 companies were selected, yielding 2025 units of analysis. The food and beverage sector was chosen for its stable demand, despite challenges such as strict regulations, fluctuations in raw material prices, and growing health and sustainability awareness. The analytical tools used to test the hypotheses were multiple regression and moderating-variable regression analyses in IBM SPSS 26. The results of the study indicate that firm size, managerial ownership, and conflict of interest do not affect accounting conservatism. Leverage is unable to moderate the relationship between firm size and managerial ownership on accounting conservatism. However, leverage moderated the effect of conflict of interest on accounting conservatism, weakening it. The results of the study indicate that firm size, managerial ownership, and conflict of interest do not affect accounting conservatism. Leverage is unable to moderate the relationship between firm size and managerial ownership on accounting conservatism. However, leverage can moderate the effect of conflict of interest on accounting conservatism, thereby weakening it. The results of this study indicate that a larger size does not guarantee that a company will apply the principle of conservatism. Managerial decisions and internal company policies often have a greater influence than size. Managerial ownership also cannot explain how accounting conservatism is applied, because low managerial ownership makes managers less conservative in preparing financial statements. Company managers currently receive bonuses because of their sense of ownership of the company, not only because of increased profits. A conflict of interest within the company does not always affect accounting conservatism, depending on specific conditions. When a company has low debt, management may feel freer to make more optimistic decisions because they do not face financial pressure from creditors, thereby reducing conflicts of interest.